Greenhouse gas emissions and energy consumption in asphalt plants - Santos, Maicon Basso dos; Candido, Jefferson; Baulé, Sofia de Souza; Oliveira, Yuri Mello Müller de; Thives, Liseane Padilha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Hot-mix asphalt used in pavement layers is produced by asphalt plants. In Brazil, despite the fact that these industrial units produce greenhouse gases, no control or measurement protocol has yet been established. This study aims to quantify emissions in different asphalt plants, in terms of carbon dioxide equivalent (CO2eq) and energy consumption. Asphalt plants were selected according to their type (batch or drum mix); production capacity (80 to 340 t/h), and whether mobile or fixed. In each plant, emissions were quantified and the energy consumption spent on drying and heating aggregates in the dryer drum was evaluated. The fuels used in the drier drum such as low pour point (LPP) oil, liquefied petroleum gas (LPG), and natural gas (NG) were evaluated and compared. The methodology consisted of surveying the thermal power of the dryer drum specified on the suppliers' catalog to calculate the volume of fuel required per ton of asphalt mixture produced. Based on the criterion of the lower calorific value of each fuel, the volume of fuel used was calculated according to the production of the asphalt plants. Through the GHC protocol tool, the quantification of emissions of carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) gases was obtained, and then transformed into CO2eq emissions. As a result, lower energy consumption was observed in the mobile batch plants and higher consumption in the mobile counterflow drum mix plants. On average, 27.69% less energy per ton of processed aggregate was needed compared to the mobile counterflow plants. The use of natural gas in the dryer drum and for all plant models was the least emissive fuel. The results showed that for the mobile batch type with a capacity of 140 t/h, the emission was 13.62 kg of CO2eq / t. On the other hand, with the mobile counterflow type with a capacity of 200 t/h, 13.64 kg of CO2eq/t was produced. Finally, with the fixed counterflow type with a production capacity of 240 t/h and 300 t/h, emissions of 13.67 kg of CO2eq/t were obtained. Through this study, the mobile batch plant with a capacity of 140 t/h using natural gas showed the least environmental impact. When natural gas was used, this model obtained energy consumption and emissions 54.5% lower than the mobile counterflow model with a capacity of 50 t/h which showed the worst environmental performance.